Exploration of the Impact of MSMEs on Increasing Exports - Cheryl Vania; Hanum Ervina (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to explore the impact of Micro, Small and Medium Enterprises on increasing exports in the context of the global economy. With the increasingly rapid growth of MSMEs, the role of this sector in increasing a country's exports has become an important subject to understand in depth. The research results show that MSMEs have a significant positive impact on increasing exports. Factors such as product innovation, global market access through digital platforms, and sustainability in the supply chain are the main drivers in MSMEs' contribution to exports. These findings provide a deeper understanding of the crucial role of MSMEs in driving the economy and increasing a country's competitiveness in international markets.